On Scheduling Tasks with Associated Linear Loss Functions - Schild, Albert; Fredman, Irwin J. (Management Science, 1961)
In a recent paper in Management Science, Robert McNaughton has discussed certain problems encountered in scheduling tasks on one or more processors when penalties are imposed if the tasks are finished after their respective deadlines. In this paper, the general problem of scheduling the tasks on one processor in order to minimize the total loss is solved, and McNaughton's results are generalized.